Early extrusion and infection of ventilation tubes of otitis media with effusion; alpha-mannosidosis: A report of two siblings - Ersozlu, Tolga; YILDIRIM, YAVUZ SELİM; YILDIRIM, YAVUZ SELİM (My University, 2013)
Alpha-mannosidosis is an autosomal recessive lysosomal storage disease caused by deficiency of the enzyme acid-mannosidase. We present a case of two children with alpha-mannosidosis and bilateral recurrent serous otitis media. Six years of female and four-year-old male siblings referred to our department of otolaryngology clinic with fluid in the middle ear. Both of them had large head with prominent forehead, flat and wide nasal bridge, mental retardation, widely spaced teeth. Based on the otolaryngological examination and tests the pre-diagnosis of alpha-mannosidosis was suspected. Measuring acid alpha-mannosidase activity in leukocytes made for diagnosis. If the patient have early extrusion and infection of ventilation tubes of otitis media with effusion and other syndromally findings, one should take into account alpha-mannosidosis. (C) 2013 Elsevier Ireland Ltd. All rights reserved.